Enhancing Mobility - Validation of Prior Nonformal and Informal Learning and Its Impact : Qualitative Insights from Germany and Poland. (1st March 2019) - Laudenbach, Franziska; Lis, Aleksandra
The validation of prior non-formal and informal learning (VPL) is central to the labour-market opportunities and educational perspectives for individuals disadvantaged in the labour market such as low-skilled, unemployed and migrant workers. VPL is seen and conceptualised as a tool to enhance social inclusion and labour-market mobility of individuals of all age groups. At the same time, it increases the transparency and usability of informal learning outcomes. This can be a means of overcoming precarious employment and working conditions. Going beyond the policy level, it is necessary to focus on the benefit to the individual of a validation process. This paper emphasises the advancement and effectiveness of VPL policies and practice in Germany and Poland. Moreover, it particularly scrutinizes how VPL initiatives benefit the individual. By introducing biographical perspectives into the validation process, the paper links institutional VPL practice with the concrete benefits to individuals who have started or completed a validation process. This gives an insight into the impact validation processes have at the level of the individual, in particular in terms of their labour-market opportunities and perspectives of broader educational pathways.